Spectral characteristics of rice (Oryza sativa L.) plantations under lying down conditions caused by wrinkle grass (Ischaemum rugosum Salisb.) - Guillén-García, Carlos Enrique (2021)
In Venezuela and worldwide, rice is a staple cereal that satisfies the caloric requirements of human beings.  The productivity of this crop is significantly affected by weeds, among which Ischaemum rugosum Salisb. stands out due to its capacity of inducing modifications in the canopy geometry of rice plants, a disadvantageous condition termed lying down.  The latter plant architecture alteration is analyzed and compared to that of a healthy rice plantation by means of spectral behavior analysis employing Sentinel 2A imagery.  Under lying down conditions, the reflectance of rice plantations increases significantly in the red band (B4) whilst decreasing in near-infrared bands, the latter effect is characteristically detected at the beginning of the flowering phase, approximately 88 days after sowing. The use of vegetation indices (VIs), particularly RVI and NDVI, allowed differentiating healthy from lying down-afflicted rice plantations; the mayor discrimination spectral bands correspond to B4 in the visible region and B11 and B12 in the mid-infrared region.